Study on P-V Curve and V-Q curve of an unbalanced three- phase system with different static loads [Analiza krzywych P-W i V-Q w niezrwnowa?onym uk?adzie trjfazowym o r?nych obci??eniach statycznych] - Ramasamy A.K.; Verayiah R.; Abidin I.Z.; Gunalan S.; Perumal P. (Wydawnictwo SIGMA - N O T Sp. z o.o., 2023)
P-V curve and V-Q curve (often term as Q-V curve) are widely used for planning and operation studies. The P-V curve and V-Q curve of an unbalanced three-phase system, unlike the balanced three-phase system, may not have similar loading margin (LM) and reactive power margin (RPM) on each phase. Therefore, DIgSILENT Programming Language (DPL) has been used to study the maximum loading point (MLP), critical point (CP), and also minimum reactive power point (MRPP) on each phase of an unbalanced three-phase system with different static loads. The tracing direction of P-V curve of each phase and the LM and RPM of each phase obtained from the P-V curve and V-Q curve for different static loads are also discussed. On top of that, continuation power flow (CPF) has become a common method to study the MLP. Hence, a simple 2-bus balanced three-phase system is used to validate the result obtained from the DIgSILENT with CPF method. 2016, Wydawnictwo SIGMA - N O T Sp. z o.o. All rights reserved.